ANALISA PENGENDALIAN PERSEDIAAN GUDANG BARANG JADI DENGAN ANALISA ABC PADA PERUSAHAAN CAT PT. PR - Dian Friana Hidayat; Ossa Sutaarga; Akhmad Fakhrurozi (Program Studi Teknik Industri Universitas Muhammadiyah Tangerang, 2019)
This research was conducted at a company that produces paints such as wall paint, tile paint, floor paint, steel construction paint and many other types of paint. In addition to these types of paint, color and size are additional factors that cause high product variants. Inventory management with ABC analysis is very necessary to control a number of inventories by taking into account the value of the investment. Based on company conditions and literature, the purpose of this study is to be able to classify inventory in the company and be able to determine inventory control based on ABC classification. The research method is divided into four stages, namely data formulation, data collection, data processing, and analysis and conclusions. Data processed is in 2016, available product variants are 941 items with a total product value of Rp 15,477,094,182.00. The results of ABC analysis are 124 product items or 13.18% A class, 211 product items or 22.42% B class, and 606 product items or 64.40% C class of the total number of products available.Key words : Paint, Inventory Control, ABC Classification